Induction of Allotriploidy in Pangasius and Its Effects on Growth Performance Through Tetraploid × Diploid Hybridization - Urabi, Debby; Rahmi, Kurnia Anggraini; Carman, Odang; Sudrajat, Agus Oman; Arfah, Harton (Jurnal Perikanan Universitas Gadjah Mada, 2025)
Triploidization is a polyploidization technique used to produce fish with improved growth, while hybridization is another method to enhance genetic quality through crosses within or between species. This study evaluated the growth performance of allotriploid catfish at the seed stage. The experiment was conducted for 45 days at the Laboratory of Reproduction and Genetics of Aquatic Organisms, Bogor Agricultural University, using a completely randomized design with four treatments and three replications. The treatments consisted of allotriploid, autotriploid, hybrid diploid, and diploid fish. Ploidy analysis showed that allotriploid and autotriploid fish had up to three nucleoli per cell, while hybrid diploid and diploid fish had a maximum of two. Growth results indicated that allotriploid fish achieved the highest final weight (4.68±0.12 g) and length (2.79 ± 0.16 inches), followed by hybrid diploid, autotriploid, and diploid fish. ANOVA results confirmed significant differences in final weight and length among treatments, indicating that ploidy manipulation and hybridization had a substantial impact on growth. However, feed conversion ratio and survival rate did not differ significantly (P > 0.05). Overall, the findings indicate that allotriploid catfish seeds showed superior growth performance compared to autotriploid, hybrid diploid, and diploid fish.